2020
DOI: 10.35940/ijitee.c7957.019320
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Size and Arrangement Effects of Petung Bamboo Split Fiber to the Matrix Interface Bond with Laminated Bamboo Split Fiber as Construction Materials for Wooden Vessels

Abstract: Bamboo is an extraordinary natural material. Bamboo can grow quickly, is cheap and widely available. The material property is light but harder and stronger than wood or glass fiber composites. The purpose of this study was to determine the effect ofarrangement and size of petung bamboo split fiber to the matrix interface bond of laminated bamboo split fiber. The benefits of this study can contribute knowledge and innovation to the development of science in the field of vessel material technology in education f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It can be used on ships' ivory, leather, decks, masts, deck boards, girders, and above-water construction. Another study also found that the thinner the thickness of the bamboo lamina applied for ship structures, the greater the value of the interfacial/ bond strength [10]. Another study discussed imp- [10].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It can be used on ships' ivory, leather, decks, masts, deck boards, girders, and above-water construction. Another study also found that the thinner the thickness of the bamboo lamina applied for ship structures, the greater the value of the interfacial/ bond strength [10]. Another study discussed imp- [10].…”
Section: Introductionmentioning
confidence: 96%
“…Another study also found that the thinner the thickness of the bamboo lamina applied for ship structures, the greater the value of the interfacial/ bond strength [10]. Another study discussed imp- [10]. Another study discussed imp-.…”
Section: Introductionmentioning
confidence: 97%